2021
DOI: 10.1016/j.ejmech.2021.113766
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and structure-activity relationship studies of 4-indole-2-arylaminopyrimidine derivatives as anti-inflammatory agents for acute lung injury

Abstract: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS), a clinically high mortality disease, has not been effectively treated till now, and the development of anti-acute lung injury drugs is imminent. Acute lung injury was efficiently treated by inhibiting the cascade of inflammation, and reducing the inflammatory response in the lung. A series of novel compounds with highly efficient inhibiting the expression of inflammatory factors were designed by using 4-indolyl-2-aminopyrimidine as the core skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is facilitated following the activation of second messengers including cAMP and cGMP and related signaling pathways including NFκB signaling and the PI3K/Akt pathway (6). Although numerous studies have previously revealed that inflammatory factors including TNF-α and IL-6 can become activated during ALI (7)(8)(9), the use of anti-inflammatory drugs (such as sivelestat and simvastatin) in clinical practice was not able to effectively reduce the mortality rate which is estimated as 30-40% globally (10). To date, no effective prevention or treatment measures exist for septic ALI (11).…”
Section: Introductionmentioning
confidence: 99%
“…This is facilitated following the activation of second messengers including cAMP and cGMP and related signaling pathways including NFκB signaling and the PI3K/Akt pathway (6). Although numerous studies have previously revealed that inflammatory factors including TNF-α and IL-6 can become activated during ALI (7)(8)(9), the use of anti-inflammatory drugs (such as sivelestat and simvastatin) in clinical practice was not able to effectively reduce the mortality rate which is estimated as 30-40% globally (10). To date, no effective prevention or treatment measures exist for septic ALI (11).…”
Section: Introductionmentioning
confidence: 99%
“…Further, compound 21 b inhibits the phosphorylation of p-38 and ERK in the MAPK signaling pathway (Figure 13). [120] Kalčic et al reported the synthesis and anti-inflammatory activity of 5-butyl-4-(4-benzyloxyphenyl)-6-phenylpyrimidin-2-amine, and their difluorinated analogs. Compounds (22 a, and 22 b) have shown inhibition of PGE2 production nanomolar in comparison with compound 22 c which displayed activity at IC 50 of 4.83 μM.…”
Section: Pyrimidines As Anti-inflammatory Agentsmentioning
confidence: 99%
“…Furthermore, to suggest a possible relationship between anticancer effects and to investigate the antioxidant properties, DPPH and ABTS tests were performed, together with fluorescence assays on 3T3-L1 cells. synthesized and 4-indole-2arylaminopyrimidine derivatives as anti-inflammatory agents for acute lung injury [31]. Compounds 6c and six h showed superior activity, and the inhibition rate of IL-6 and IL-8 release ranged from 62% to 77% and from 65% to 72%, respectively.…”
Section: Fig 16: Synthesis Of New Indole-benzimidazoles (23-59)mentioning
confidence: 99%